Utilization of sewage sludge as fertilizer for silver vase bromeliad - Zabotto, Alessandro Reinaldo [UNESP]; Longuini Gomes, Leticia Danielle; Villas Boas, Roberto Lyra [UNESP]; Siqueira, Matheus Casarini; Young, Jorge Luiz Marx; Kanashiro, Shoey; Tavares, Armando Reis (Taylor & Francis, 2024)
Sewage sludge (SS) is a source of nutrients, and it improves the physical, chemical, and biological properties of soil, thereby increasing crop productivity. Accordingly, this study was aimed to evaluate the growth and development of the silver vase bromeliad (Aechmea fasciata) cultivated in a substrate with different doses of SS. To accomplish this, silver vase bromeliad plants were cultivated for 120 days in pots containing pine bark as a substrate with varying doses of solid SS (0, 18, 36, 54, or 72 g SS L−1). The experiment was carried out in a completely randomized block design, comprising five treatments and four replications, with four plants per pot, totaling 80 plants. Substrate fertilization with SS improved the nutritional status as well as the physiological and morphological parameters of the silver vase bromeliad. Fertilization with 72 g SS L−1 added to pine bark resulted in the best outcomes for plant height and the number of leaves.
Keywords: Aechmea fasciata; epiphytic bromeliad; fertilization; organic nutrition; pine bark